Corak Kerukunan Umat Kristen dan Umat Islam di Kelurahan Naikolan - Marmiati Mawardi (Analisa: Journal of Social Science and Religion, 2009)
Naikolan is name of one village in the city of Kupang, East Nusa Tenggararegion. In the area stood a mosque and a tomb where Muslims are located sideby side with people of non-Muslim graves. Places of worship and the tombbecame a symbol of harmony between faiths, because both places are givingreligious Kupang King Christian to it Muslim relatives. The mosque was theembryo of the Muslim community in Kupang that the mosque neighborhoodknown as the Muslim village. Adhesives of Nailokan harmony is kinship andthe Love motto of Kupang.Keywords: Harmony, Kinship, Motto Kupang.